A novel approach for assessing effects of ship traffic on distributions and movements of seabirds. (1st December 2019) - Burger, Claudia; Schubert, Alexander; Heinänen, Stefan; Dorsch, Monika; Kleinschmidt, Birgit; Žydelis, Ramūnas; Morkūnas, Julius; Quillfeldt, Petra; Nehls, Georg
Abstract: Marine habitats are nowadays strongly affected by human activities, while for many species the consequences of these impacts are still unclear. The red-throated diver ( Gavia stellata ) has been reported to be sensitive to ship traffic and other anthropogenic pressures and is consequently of high conservation concern. We studied red-throated divers in the German Bight (North Sea) using satellite telemetry and digital aerial surveys with the aim of assessing effects of ship traffic on the distribution and movements of this species during the non-breeding season. Data from the automatic identification system of ships (AIS) were intersected with bird data and allowed detailed spatial and temporal analyses. During the study period, ship traffic was present throughout the main distribution area of divers. Depending on impact radius, only small areas existed in which ship traffic was present on less than 20% of the days. Ship traffic was dominated by fishing vessels and cargo ships, but also wind farm-related ships were frequently recorded. Red-throated divers were more abundant in areas with no or little concurrent ship traffic. Analysis of aerial survey data revealed strong effects of ship speed on divers: in areas with vessels sailing at high speed only a slow resettlement of the area was observed after the disturbance, while in areas with vessels sailing at medium speed the resettlement was more rapid during the observed time period of 7 hours. Data from satellite-tracking of divers suggest that large relocation distances of individuals are related to disturbance by ships which often trigger birds to take flight. Effective measures to reduce disturbance could include channeled traffic in sensitive areas, as well as speed limits for ships traveling within the protected marine area. Highlights: Divers ( Gavia stellata ) show strong aversive responses towards ship traffic. Partial resettlement was observed within 7 hours after disturbance by ships. The disturbance effect was stronger when high-speed-vessels had passed. Ship encounters were related to greater individual movements of divers. Channeled ship traffic and speed limits are recommended to reduce disturbance.